2011
DOI: 10.30539/iraqijvm.v35i2.572
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Antibacterial Properties for Some Iraqi Plants Against Salmonella typhimurium

Abstract: This study was include the investigation of the antibacterial activity of ethanolic extract for (12) type of Iraqi plant leaves (Allium porrum L, Apium graveolens Mill., Cassia angustifollia Vahl., Lawsonia inermis L., Lepidium sativum L., Malva sylvestris L., Monthapiperita L., Ocimmum bassillicum L., Pettroselinum crispum Mill., Raphanus sativus L., Sponacia oleraceal. and Trigonella foenum L.). In different concentrations (20, 40, 60, 80, 100) mg/ml against Salmonella typhimurium in vitro using agar well di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…The potent antibacterial potential of M. sylvestris, as witnessed in the present study, agrees with the reports on it against various bacteria, including Salmonella (29,30). Moreover, the MIC/MBC of M. sylvestris extract against the standard and clinically isolated Salmonella enterica from diarrheic lambs in Urmia, Iran, were reported to be 50/100 and 42/80 mg/mL, respectively (31).…”
Section: The H Sabdariffa Calyx Extract Efficacy Againstsupporting
confidence: 91%
“…The potent antibacterial potential of M. sylvestris, as witnessed in the present study, agrees with the reports on it against various bacteria, including Salmonella (29,30). Moreover, the MIC/MBC of M. sylvestris extract against the standard and clinically isolated Salmonella enterica from diarrheic lambs in Urmia, Iran, were reported to be 50/100 and 42/80 mg/mL, respectively (31).…”
Section: The H Sabdariffa Calyx Extract Efficacy Againstsupporting
confidence: 91%
“…This may be due to the fact that T6 (nisin 150 mg/kg + 3% sodium lactate) treatment is the best in inhibiting the total number of bacteria, psychrophilic bacteria and coliform bacteria. As for the periods of cold storage, table (7) shows a significant increase (P˂0.01) in the logarithm of the total number of bacteria in the period 12, 8 and 4 days as compared to the period 0 days of cold storage and this results came in agreement with those of (10, 13,25,34,36). It is noted from the results that the total number of bacteria for all addition treatments was within permissible limits for the total count of bacteria in meat by the Iraqi Central Organization for Standardization and Quality Control (7 logarithmic cycles) (16).…”
Section: Table 1 Effect Of Nisin Potassium Sorbate and Sodium Lactate...supporting
confidence: 79%
“…In a study conducted by Shadid et al (13), the acetonic extract of M. sylvestris exhibited strong antibacterial activity against Proteus vulgaris and S. aureus with the MIC values of 0.078 and 0.125 mg/mL, respectively. Other studies have also shown the cytotoxic properties of M. sylvestris extract against Salmonella enterica serovar Typhimurium (14), Listeria monocytogenes (15), Bacillus cereus (15), methicillin-resistant S. aureus (MRSA) (11), Aggregatibacter actinomycetemcomitans (10), and Candida species (16). The limitation of previous studies is that in all these studies, only the antimicrobial properties of the extract were investigated, and its anti-biofilm properties on pathogenic bacteria were not evaluated.…”
Section: Introductionmentioning
confidence: 98%